The prospects for an imminent demographic dividend in Africa: The case for cautious optimism - Alaka M. Basu; Kaushik Basu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper looks at the prospects of a demographic dividend in Africa in the near future. While acknowledging that the fertility declines which change population age structures and thus dependency ratios have been slow to begin and often seem to have stalled once they have begun, we nevertheless conclude that there are many underlying features of Africa today which might hasten the process. These features have to do with some of the preconditions under which fertility fell in other parts of the world - such as economic development, social modernization, mortality decline and a rise in 'natural' fertility - but also include the fact that the global world today is again, after a hiatus, interested in and proactively working towards investments in voluntary family planning. All these conditions are conducive to faster fertility decline than in the past and with the right policies could allow the region to exploit this demographic window of opportunity. We also comment on some of the economic implications of a demographic dividend in Africa, including the helpful fact that when it occurs, the economic impact of a relatively larger labour force may be enhanced because of, unlike in some other parts of the world, the historical and cultural acceptance of women in the labour force.
Keywords: E0; J11; J13; I11; 330; Africa; age distribution; family planning; health